Biospeleothems Formed by Fungal Activity During the Early Holocene in the “Salar de Uyuni” - Anglés, Angélica; He, Qitao; Sánchez García, Laura; Carrizo, Daniel; Rodriguez, Nuria; Huang, Ting; Shen, Yan; Amils, Ricardo; Fernández-Remolar, David C. (Frontiers in Microbiology, 2022)
The Chiquini and Galaxias caves contain speleothems that are templated by long fungal structures. They have been associated with the carbonate lacustrine deposits in the margins of the Coipasa and Uyuni Salar basins. During a wetter episode, such carbonates formed at the end of the last glaciation raising the lake level to more than 100 m in the Tauca events (15–12 ky). Such an event flooded the caves that eventually became a cryptic habitat in the lake. The caves show bizarre speleothems framed by large (>1 m) fungal buildings covering the older algal mineralized structures. Although the origin of the caves is not fully understood, the occurrence of two carbonatic units with very distinctive fabric suggests that they formed in two separated humid events. In this regard, the mineralized algal structures, showing the same features as the lacustrine carbonates, likely formed during the Tauca flooding events in the terminal Pleistocene that inundated older caves. The different caves were exposed to the atmosphere after a drop in the lake level that promoted alluvial erosion by <12–10 ky (Ticaña episode) under arid conditions. A last humid episode rising the lake surface 10 m above the Salar level, which was not enough to inundate the caves a second time, drove the formation of the biospeleothems by fungi biomineralization. The abundance and size of the preserved fungal structures suggest that they were sustained by a stable hydrological activity plus a constant organic supply. While nutrients could have been primarily sourced from the vegetal communities that occupied the exhumated lake margins, they might have also been released from the lacustrine carbonatic unit. The combination of hydrology and biological activities were likely determinants for a fast rock dissolution and mineralization ending in the construction of the fungal biospeleothems.